The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1001/archpsyc.58.10.925
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Correlates of Depression After Ischemic Stroke

Abstract: Lesions affecting the prefrontosubcortical circuits, especially on the left side, are correlates of depression after ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
122
3
21

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 48 publications
5
122
3
21
Order By: Relevance
“…In subsequent studies, Starkstein et al, 4 Astrom et al, 5 Morris et al, 6 Herrmann et al, 7,8 Vataja et al, 9,10 all found significant associations between left frontal and/or left basal ganglia lesions and major poststroke depression. Furthermore, Bolla-Wilson et al 11 and Spalletta et al 12 found an association between major depression in patients with left hemisphere stroke and cognitive impairment, while Spalletta 13,14 found an association between unawareness of emotions and right hemisphere stroke.…”
Section: Introductionmentioning
confidence: 93%
“…In subsequent studies, Starkstein et al, 4 Astrom et al, 5 Morris et al, 6 Herrmann et al, 7,8 Vataja et al, 9,10 all found significant associations between left frontal and/or left basal ganglia lesions and major poststroke depression. Furthermore, Bolla-Wilson et al 11 and Spalletta et al 12 found an association between major depression in patients with left hemisphere stroke and cognitive impairment, while Spalletta 13,14 found an association between unawareness of emotions and right hemisphere stroke.…”
Section: Introductionmentioning
confidence: 93%
“…Entre as áreas acometidas relacionadas à DPAVC, destacam-se a região frontal esquerda e os gânglios da base (caudado, putâmen, pálido) 7,68 . Uma das hipóteses aventadas é a de que o acometimento do circuito prefrontosubcortical seria o responsável pela ocorrência do transtorno depressivo maior 69 .…”
Section: Localização Do Avcunclassified
“…Uma das hipóteses aventadas é a de que o acometimento do circuito prefrontosubcortical seria o responsável pela ocorrência do transtorno depressivo maior 69 . Ao comparar pacientes com e sem DPAVC, utilizando ressonância magnética de forma sistemática, o estudo de Vataja et al 7 verificou que os pacientes com depressão tinham infartos com mais frequência, afetando o circuito prefrontosubcortical ou algumas de suas estruturas: caudado, pálido, joelho da cápsula interna e cápsula anterior, especialmente no HE. O AVC na região da amígdala, apesar de raro, foi considerado super-representativo, pois cinco dos únicos seis pacientes com infarto nesta região estavam deprimidos.…”
Section: Localização Do Avcunclassified
See 1 more Smart Citation
“…Ao comparar pacientes com e sem depressão pós-AVC, utilizando ressonância magnética de forma sistemática, o estudo de Vataja et al 40 verificou que os pacientes com depressão tinham com mais freqüência infartos afetando o circuito prefrontosubcortical ou algumas de suas estruturas: caudado, pálido, joelho da cápsula interna e cápsula anterior, especialmente no HE. O AVC em região da amígdala, apesar de raro, foi considerado super-representativo, pois cinco dos únicos seis pacientes com infarto nesta região estavam deprimidos.…”
Section: Localização Neuroanatômicaunclassified